(3QSGdI aj RjGOGJ CHj Sgd Ydi cJGH GdeYWjGJ dEbdjOSs - (3nhrjnLf Hf QSJe Gdochgj (B( (3Gdbhgj (B) (3, CHh Sgd,J (B390 (3g` s
(3ChdgG (B:s
(3EPG cGfJ ebGOjQ hcGfJ fSHI cd hGMO efgG Edi BNQ eYdheI aEf fSHI LejYgG Edi Pdc GdebOGQ eYdheI s
(3BNQgG (B:s
(3hCeG Cf jchf CMOgeG GYXe ef ebOGQ fSHJg Edi GdBNQ eYdheI HTF eYdhe hPdc eG CQOfG Cf fHjf JeJ GdCTcGd s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdJGSY YTQs
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B127 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B175s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
Keywords: (3GdQjGVjGJs